Gestión administrativa simultánea al proceso de enseñanza aprendizaje en escuelas unidocentes del circuito 05H00D02C2-03 cantón La Maná. Diseño de una estrategia activa pedagógica. - Lara Alvarez, Jeanette Alexandra (2016)
The present research is focused on the implementation of pedagogical active strategies in one-teacher schools. It is applied by detecting deficiencies in managing both teaching and learning processes and administrative management in parallel way, so the achievement of learning in students can decrease and can show themselves at a greater disadvantage to other students just because of the double role of teachers in these schools. This fact motivated to provide teachers with the knowledge and application of new active teaching strategies in order to improve the teaching and learning process. According this point of view, it could not be ignored to contribute in a modest way something constructive for the institution we owe to, so it is an active teaching strategy that contributes to improve the quality of education in these institutions. That was why there is a new vision of educational changes in which the importance of the whole center as a fundamental factor in achieving those goals. In this context, the actions to be planned and executed in the institution, administrative and educational area should be aimed in achieving the expressed objectives, so this research aims to contribute to the actual visualization of these aspects. At the same time, to generate a concrete proposal to strengthen the positive findings and to beat the weaknesses in relation to administrative and educational management, with the coordination of actions which are defined to achieve efficiency and efficacy at educational management, so improving the teaching and learning process.